ACSS2 and metabolic diseases: from lipid metabolism to therapeutic target - Alaa El-Kurjieh; Reem Al-Arab; Qamar Abou Hachem; José-Noel Ibrahim; Philippe Hussein Kobeissy (Lipids in Health and Disease)
Abstract Elevated incidence of metabolic disorders has been reported worldwide in the recent decade, highlighting the need for developing efficient therapies. These diseases result from a complex interplay of various factors that contribute to disease progression, complications, and resistance to current treatment options. Acetyl-CoA Synthetase Short Chain Family Member 2 (ACSS2) is a nucleo-cytosolic enzyme with both lipogenic and metabolic regulatory roles. Studies on ACSS2 have shown that it is involved in pathways commonly dysregulated in metabolic disorders, leading to fat deposition and disrupted cellular signaling. Although multiple studies have suggested a role of ACSS2 in the metabolic rewiring during tumorigenesis, few studies have examined its involvement in the pathophysiology of metabolic diseases. Recent evidence indicates that ACSS2 may contribute to the pathogenesis of various metabolic disorders making its examination of great interest and potentially aiding in the development of new therapeutic strategies. The objective of this review is to summarize the current understanding of ACSS2’s role in metabolic disorders and its potential as a therapeutic target.